2014
DOI: 10.1523/jneurosci.3448-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dscam1 Is Required for Normal Dendrite Growth and Branching But Not for Dendritic Spacing inDrosophilaMotoneurons

Abstract: Down syndrome cell adhesion molecule, Dscam, serves diverse neurodevelopmental functions, including axon guidance and synaptic adhesion, as well as self-recognition and self-avoidance, depending on the neuron type, brain region, or species under investigation. In Drosophila, the extensive molecular diversity that results from alternative splicing of Dscam1 into Ͼ38,000 isoforms provides neurons with a unique molecular code for self-recognition in the nervous system. Each neuron produces only a small subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…In 60% of all preparations it abolishes more than 90% of all dendrites and leaves the primary neurite decorated with lamellipodia-like structures (Fig. 1C) (26). In the remaining 40% of all preparations it reduces dendritic length and branching to 50% of controls (26) (see Fig.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…In 60% of all preparations it abolishes more than 90% of all dendrites and leaves the primary neurite decorated with lamellipodia-like structures (Fig. 1C) (26). In the remaining 40% of all preparations it reduces dendritic length and branching to 50% of controls (26) (see Fig.…”
Section: Resultsmentioning
confidence: 92%
“…MN5 can be unambiguously identified from animal to animal and displays a stereotyped dendritic morphology comprising a total length of 6,500 μm and >4,000 branches (13). Dendritic architecture is tightly regulated during development by steroid hormones (24), calcium signaling (25), neural activity (19,20), and cell surface signals (26). We have previously shown that the Significance Approximately 100 billion neurons in our brain form 100 trillion synapses onto 100,000 miles of dendritic cable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations